A Joint Elliott Type Theorem for Twists of L-Functions of Elliptic Curves - Garbaliauskienė, Virginija; Laurinčikas, Antanas (Mathematical Modelling and Analysis, 2016)
We consider a collection of L-functions of elliptic curves twisted by a Dirichlet character modulo q (q is a prime number), and prove for this collection a joint limit theorem for weakly convergent probability measures in the space of analytic functions as q → ∞. The limit measure is given explicitly.